Designing an innovative primary health care model for the Iranian health system: A mixed methods study protocol - Solmaz Azimzadeh; Jafar Sadegh Tabrizi; Saber Azami-Aghdash; Kamal Gholipour (Elsevier, 2023)
Introduction: Today, the main strategy of countries to improve the health status of people is primary health care (PHC). The present study has two main objectives: 1) scoping review and mapping of the characteristics of innovative PHC models in different countries, 2) developing and validating a model for innovative PHC considering the PHC conditions and challenges of the Islamic Republic of Iran. Methods: The study will be performed in five phases. In this regard, first, a scoping review will be conducted to investigate the characteristics of innovative PHC. Second, a qualitative study will be performed on the PHC challenges in Iran. Third, another qualitative study will be conducted to identify the appropriate components for Iran's innovative PHC system, using the opinions of experts in this field. In the fourth phase, using the panel of experts, a suitable model will be designed for the Iranian PHC system. Eventually, in the fifth phase, the goals and components of the model developed by experts will be evaluated through a Delphi study, and the validity of the model will be measured using appropriate criteria. Results: The findings of this research provide considerable insight into how Iran's PHC system will be able to consider innovative models and changes in response to a new context and newly emerged problems. Conclusion: Given the importance of PHC in the present era and the need to pay more attention to and strengthen it for all communities, it seems necessary to conduct studies and provide appropriate conditions for the development of PHC.